The Influence of Employer Branding and Employee Value Proposition on Employee Retention with Employee Engagement as Mediation - Pradita, Yossy Eka; Hana Setyanti, Sri Wahyu Lelly; Mufidah, Ana (International Journal of Scientific Research and Management (IJSRM), 2024)
Human resources are the most important aspect in carrying out management activities. In order to realize this, an employee retention level is needed in an organization. This research aims to test and analyze whether, Employee Value Proposition, and Employee Engagement have a significant effect on Employee Retention, as well as whether Employee Engagement can mediate the influence between Employer Branding and Employee Value Proposition on Employee Retention. The total population in this study was 47 respondents with a total sample taken using saturated sampling of 42 respondents, because there were several employees who were continuing their education. The respondents in the sample were employees of the Bank Indonesia Jember Regional Representative Office with permanent employee status. The type of data used is quantitative qualitative data. The data source used is primary data, where this data is obtained from the results of respondents' direct answers through research questionnaires and interviews. The data analysis method used in this research is Path Analysis with the help of IBM SPSS Statistics 26.0 software. The results of this research show that Employer Branding, Employee Value Proposition, and Employee Engagement have a significant effect on Employee Retention, and Employee Engagement can mediate the influence between Employer Branding and Employee Value Proposition on Employee Retention.